1981
DOI: 10.1103/physreva.23.2537
|View full text |Cite
|
Sign up to set email alerts
|

Electron orbits and stability in realizable and unrealizable wigglers of free-electron lasers

Abstract: Magnetostatic wiggler fields x coskz +y" sinkz, commonly used to model the undulators of free-electron lasers, violate Maxwell's equations and are "unrealizable. " Realizable wigglers that approximate the unrealizable ones near the axis have a radial variation and an axial field component, both of which affect electron motion. Exact helical equilibrium orbits are given for relativistic electrons in a combined uniform guide field and realizable wiggler, in cylindrical geometry. The parameter ka that measures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Indeed, the surface-of-section plots show that the regular region of phase space diminishes in size as the wiggler amplitude is increased. In the limit where self-field effects are negligibly small, it is found that the onset of chaoticity for electron orbits with guiding center on the axis of the wiggler helix occurs whenever for the existence of helical, steady-state orbits for given electron energy Yb (Diament, 1981). Furthermore, it is shown that the onset of chaoticity for off-axis electron orbits occurs at some values of A less than Ac(0).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, the surface-of-section plots show that the regular region of phase space diminishes in size as the wiggler amplitude is increased. In the limit where self-field effects are negligibly small, it is found that the onset of chaoticity for electron orbits with guiding center on the axis of the wiggler helix occurs whenever for the existence of helical, steady-state orbits for given electron energy Yb (Diament, 1981). Furthermore, it is shown that the onset of chaoticity for off-axis electron orbits occurs at some values of A less than Ac(0).…”
mentioning
confidence: 83%
“…and yo. The motion is integrable and has been analyzed by several authors (Friedland, 1980;Diament, 1981;Freund and Drobot, 1982;Davidson and Uhm, 1982;Freund, 1983;Littlejoin, Kaufman, and Johnston, 1987;Chen and Schmidt, 1988 which determines the values of P,0 = pzo/mc in terms of the parameters aw, ao, and -Yo. Equation (3.16) is a fourth-order algebraic equation for P.0, which has at most four real roots.…”
Section: A Hamiltonian In Guiding Center Variablesmentioning
confidence: 99%
“…In the above equations,B w is the magnetic field of a threedimensional helical wiggler with amplitude B A and wave number k w , which can be expressed as [5] …”
Section: Nonlinear Simulation Modelmentioning
confidence: 99%
“…Later, it was extended to a three-dimensional (3D) helical wiggler for the electrons with on-axis guiding centers [5,6]:…”
Section: Resonance and Antiresonancementioning
confidence: 99%
See 1 more Smart Citation